The war on drugs : a history - Farber, David, 1956- (New York University Press, 2022)
"Fifty years after President Richard Nixon declared a "War on Drugs," leading scholars examine how drug war policies contributed to the making of the carceral state, racial injustice, deviant globalization, regulatory disasters, and a massive underground economy; they also point the way forward to a more just and humane drug policy regime"--